2014
DOI: 10.1007/s12160-014-9664-1
|View full text |Cite
|
Sign up to set email alerts
|

The Results of the “Positive Action for Today’s Health” (PATH) Trial for Increasing Walking and Physical Activity in Underserved African-American Communities

Abstract: Background The “Positive Action for Today’s Health” (PATH) trial tested an environmental intervention to increase walking in underserved communities. Methods Three matched communities were randomized to a police-patrolled walking plus social marketing, a police-patrolled walking-only, or a no-walking intervention. The 24-month intervention addressed safety and access for physical activity (PA) and utilized social marketing to enhance environmental supports for PA. African-Americans (N=434; 62 % females; aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 40 publications
(43 reference statements)
2
86
2
Order By: Relevance
“…Null results were found in both dichotomously and continuously measured PA and included, but were not limited to no increases in leisure time physical activity, no differential increase in physical activity between experimental and control communities, no changes in the proportion of a population achieving 30 min of MVPA 5 days per week, and no difference between communities in average daily minutes of MVPA as measured by both accelerometry and 4-month recall [1]. Positive changes most likely to be observed included increased use of trails and pathways [6,9], attendance at walking programs [6], supervised leisure time activity in school-aged adolescents [10] and daily walking [11]. The four high quality studies showed no overall effect of community-PA interventions, although one [6] did observe increased walking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Null results were found in both dichotomously and continuously measured PA and included, but were not limited to no increases in leisure time physical activity, no differential increase in physical activity between experimental and control communities, no changes in the proportion of a population achieving 30 min of MVPA 5 days per week, and no difference between communities in average daily minutes of MVPA as measured by both accelerometry and 4-month recall [1]. Positive changes most likely to be observed included increased use of trails and pathways [6,9], attendance at walking programs [6], supervised leisure time activity in school-aged adolescents [10] and daily walking [11]. The four high quality studies showed no overall effect of community-PA interventions, although one [6] did observe increased walking.…”
Section: Resultsmentioning
confidence: 99%
“…Positive changes most likely to be observed included increased use of trails and pathways [6,9], attendance at walking programs [6], supervised leisure time activity in school-aged adolescents [10] and daily walking [11]. The four high quality studies showed no overall effect of community-PA interventions, although one [6] did observe increased walking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Data for our study were assessed at baseline and included height, weight, blood pressure and physical activity. Additionally, psychosocial and demographic data (age, sex, education status, annual income, occupational status, and marital status) were obtained by trained research staff.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…16,17 Specifically, our study expands on past literature by evaluating the associations of neighborhood factors (places to walk and bike, neighborhood satisfaction, perception of safety, and neighborhood social interaction) and peer support on body mass index (BMI) in African American adults. Based on previous research, it was hypothesized that neighborhood social and environmental factors would be significantly predictive of BMI in our study.…”
Section: Introductionmentioning
confidence: 99%